The Sacred Groves of Tamil Nadd - Amirthalingam, M. (Indian Forester, 2004)
The Sacred groves can be considered as a part of forests left untouched by the local inhabitants , and protected by the local village folk deities. Several such groves are reported in many parts of India. In this paper , an inventory of the intact Sacred groves of Tamil Nadu is given. Detailed information on the location , area and associated deities are available for 500 groves. Out of 500 groves 343 are dedicated to 93 different male deities and 157 are dedicated to 77 different female deities. The approximate total area occupied by the Sacred groves is 21 ,694.34 ha. These Sacred groves are only remnants of the original forest , maintained in near climax condition in many parts of Tamil Nadu. As such , these groves now play a vital role in the conservation of biological diversity.